Christisonia flavirubens (Orobanchaceae), a new species from south Western Ghats, India - Mathew, Jose; Salim, Pichan M. (Biodiversity: Research and Conservation, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*89.16px); top: calc(var(–scale-factor)*289.33px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.986267);" role="presentation">Christisonia flavirubens <span dir="ltr" style="left: calc(var(–scale-factor)*185.33px); top: calc(var(–scale-factor)*289.33px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.967412);" role="presentation">J.Mathew & P.M.Salim (Orobanchaceae), a new holoparasitic plant species from the southern <span dir="ltr" style="left: calc(var(–scale-factor)*48.19px); top: calc(var(–scale-factor)*301.33px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.989187);" role="presentation">Western Ghats, Kerala, India, is described based on morphological data. The diagnostic morphological characters, distribution <span dir="ltr" style="left: calc(var(–scale-factor)*48.19px); top: calc(var(–scale-factor)*313.33px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00031);" role="presentation">and images of the new species are presented. Images and comparative characters of the reddish yellow coloured <span dir="ltr" style="left: calc(var(–scale-factor)*498.20px); top: calc(var(–scale-factor)*313.33px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02317);" role="presentation">Christisonia <span dir="ltr" style="left: calc(var(–scale-factor)*48.19px); top: calc(var(–scale-factor)*325.33px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.997658);" role="presentation">species of the south Western Ghats are also provided for its easy identification.